Overall Structural Alteration of Gut Microbiota and Relationships with Risk Factors in Patients with Metabolic Syndrome Treated with Inulin Alone and with Other Agents: An Open-Label Pilot Study - Tian, Ruiping; Hong, Jiahui; Zhao, Jingjie; Zhou, Dengyuan; Liu, Yangchen; Jiao, Zhenshan; Song, Jian; Zhang, Yu; Meng, Lingzhang; Yu, Ming (Mediators of Inflammation, 2022)
Objective. The relative contribution of some products with prebiotic effects, such as inulin, together with medications specific to the human gut microbiome has not been comprehensively studied. The present study determined the potential for manipulating populations in the gut microbiome using inulin alone and combined with other agents in individuals with metabolic syndrome (MetS). The study also assessed whether there is relationship variability in multiple clinical parameters in response to intervention with the changes in the gut milieu. Participants/Methods. This single-centre, single-blinded, randomised community-based pilot trial randomly assigned 60 patients (mean age, 46.3 y and male, 43%) with MetS to receive either inulin, inulin+traditional Chinese medicine (TCM), or inulin+metformin for 6 months. Lipid profiles, blood glucose, and uric acid (UA) levels were analysed in venous blood samples collected after overnight fast of 8 h at baseline and at the end of the follow-up period. Microbiota from stool samples were taxonomically analysed using 16S RNA amplicon sequencing, and an integrative analysis was conducted on microbiome and responsiveness data at 6 months. Results. The results of 16S rRNA sequencing showed that inulin resulted in a higher proportion of Bacteroides at the endpoint compared with inulin+TCM and inulin+metformin (p=0.024). More Romboutsia (p=0.043), Streptococcus (p<0.001), and Holdemanella (p=0.011) were found in inulin+TCM and inulin+metformin samples. We further identified gut microbiota relationships with lipids, UA, and glucose that impact the development of MetS. Conclusion. Among the groups, inulin alone or combined with metformin or TCM altered specific gut microbiota taxa but not the general diversity. Accordingly, we analysed metabolites associated with microbiota that might provide more information about intrinsic differences. Consequently, a reliable method could be developed for treating metabolic syndrome in the future.